2008
DOI: 10.1111/j.1479-8298.2008.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Arengomyia, new genus for the Colocasiomyia arenga species group (Diptera: Drosophilidae), with description of a new species

Abstract: The arenga species group, hitherto consisting of three species, Colocasiomyia arenga, C. pararenga and C. sagittata, is separated from the genus Colocasiomyia, and established as the new genus Arengomyia Yafuso and Toda, gen. nov. Of the three species, C. pararenga Okada, 1990 is synonymized with C. arenga (Okada, 1987). A new species, Arengomyia xanthopleura Yafuso and Toda, sp. nov., is also described. Supplementary descriptions and revisions of some morphological characters are also provided for the known s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Accordingly, Yafuso et al . () established Arengomyia Yafuso & Toda, for this group. On the other hand, Sultana et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, Yafuso et al . () established Arengomyia Yafuso & Toda, for this group. On the other hand, Sultana et al .…”
Section: Resultsmentioning
confidence: 97%
“…Although Grimaldi (1991) regarded the arenga group and the toshiokai group as the first and the second branches, respectively, Sultana et al (2006) revealed the distant relationship of the arenga group to the genus Colocasiomyia. Accordingly, Yafuso et al (2008) (2006) suggested the sister relationship between the toshiokai and baechlii groups with a bootstrap value of 77.2%. However, of the characters having supported this relationship, some were regarded as symplesiomorphies and others were revised for character states in the present study.…”
Section: Cladogrammentioning
confidence: 99%
“…Anthophilic drosophilids, therefore, are present worldwide, especially in tropical regions. Other noteworthy examples are the Scaptodrosophila aterrima species group in Africa (Tsacas et al, 1988), the subgenus Exalloscaptomyza Hardy of Scaptomyza Hardy, in Hawaii (Montague & Kaneshiro, 1982;Starmer & Bowles, 1994), Scaptodrosophila hibisci (Bock) and S. aclinata (McEvey & Barker), in Australia (Cook et al, 1977;McEvey & Barker, 2001), the Drosophila elegans species subgroup (melanogaster group) (Sultana et al, 1999), the genus Colocasiomyia de Meijere (Carson & Okada, 1980;Sultana et al, 2006;Fartyal et al, 2013) and the genus Arengomyia Yafuso & Toda (Yafuso et al, 2008), in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Up to the present, 23 species of Colocasiomyia have been described exclusively from the Oriental Region including New Guinea (Sultana et al . 2006; Yafuso et al . 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Up to the present, 23 species of Colocasiomyia have been described exclusively from the Oriental Region including New Guinea (Sultana et al 2006;Yafuso et al 2008). In recent years, however, a considerable number of new species have been discovered in Southeast Asia (Sultana et al 2006;M.…”
Section: Introductionmentioning
confidence: 99%